Late-night salivary cortisol and cortisone should be the initial screening test for Cushing's syndrome. Issue 7 (27th June 2022) - Mohamed, Ramjan Sanas; Abuelgasim, Biyaser; Barker, Sally; Prabhudev, Hemanth; Martin, Niamh M; Meeran, Karim; Williams, Emma L; Darch, Sarah; Matthew, Whitlock; Tan, Tricia; Wernig, Florian
Abstract : Endogenous Cushing's syndrome (CS) poses considerable diagnostic challenges. Although late-night salivary cortisol (LNSC) is recommended as a first-line screening investigation, it remains the least widely used test in many countries. The combined measurement of LNSC and late-night salivary cortisone (LNS cortisone) has shown to further improve diagnostic accuracy. We present a retrospective study in a tertiary referral centre comparing LNSC, LNS cortisone, overnight dexamethasone suppression test, low-dose dexamethasone suppression test and 24-h urinary free cortisol results of patients investigated for CS. Patients were categorised into those who had CS (21 patients) and those who did not (33 patients). LNSC had a sensitivity of 95% and a specificity of 91%. LNS cortisone had a specificity of 100% and a sensitivity of 86%. With an optimal cut-off for LNS cortisone of >14.5 nmol/L the sensitivity was 95.2%, and the specificity was 100% with an area under the curve of 0.997, for diagnosing CS. Saliva collection is non-invasive and can be carried out at home. We therefore advocate simultaneous measurement of LNSC and LNS cortisone as the first-line screening test to evaluate patients with suspected CS.